Triacontanoic ester of 5ʹʹ-hydroxyjustisolin: Tumour suppressive role in cervical cancer via Bcl-2, BAX and caspase-3 mediated signalling. (2019) - Joseph, Litty; Srinivasan, K.K.
Graphical abstract: Highlights: is a lignan isolated from J.simplex D. Don, possesses antiproliferative and antitumor activity both in vitro and in vivo . The isolated compound selectively inhibited the growth of HeLa cells and does not produce any significant toxicity in HaCat cells. It induced cell cycle arrest at G0/G1phase. Theanti-tumour actvity is due to the downregulation of Bcl-2, upregulation of BAX and overexpression of caspase-3, which leads to apoptosis. Abstract: Triacontanoic ester of 5ʺ-hydroxyjustisolin, a lignan from Justicia simplex D. Don, possesses antitumor activity. However, the molecular mechanism underlying this is not yet clearly understood. The present study showed significant inhibition in cell viability on HeLa cell line and induced minor toxicity in normal cells. This compound induced mitotic arrest at G0/G1 phase followed by apoptosis in human cervical cancer cells and was accompanied by the upregulation of BAX, caspase-3 and downregulation of Bcl-2. Taken together, these data reveal that the title compound acts through multiple cellular/molecular pathways, which strongly suggest the role of pro and antiapoptotic Bcl-2 family proteins. Triacontanoic ester of 5ʹʹ-hydroxyjustisolin may be a potential agent for the cervical cancer treatment.